2010
DOI: 10.1158/0008-5472.can-09-3690
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Selectively Kills Tumor-Associated Myeloid-Derived Suppressor Cells Resulting in Enhanced T Cell–Dependent Antitumor Immunity

Abstract: Myeloid-derived suppressor cells (MDSC) accumulate in the spleen and tumor bed during tumor growth. They contribute to the immune tolerance of cancer notably by inhibiting the function of CD8 (+) T cells. Thus, their elimination may hamper tumor growth by enhancing antitumor T-cell functions. We have previously reported that some anticancer agents relied on T cell-dependent anticancer responses to achieve maximal efficacy. However, the effect of anticancer agents on MDSC has remained largely unexplored. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
824
3
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,039 publications
(865 citation statements)
references
References 40 publications
31
824
3
7
Order By: Relevance
“…In a Tim3 transgenic mouse model and a galectin-9 (Tim3 ligand) transgenic mouse model, an increase in MDSCs and inhibition of immune responses are observed [27]. Interestingly, we found that Tim3-hIg expressing therapeutic tumor vaccine did not exhibit an additive inhibitory effect on tumor growth when given in combination with 5-FU, which has recently been reported to selectively kill MDSCs and thus enhance antitumor immunity [33]. Second, Tim3 pathway inhibition may enhance anti-tumor immunity by antagonizing phagocytosis of apoptotic cells and thereby circumventing the immunosuppressive effect of apoptosis.…”
Section: Discussionmentioning
confidence: 66%
“…In a Tim3 transgenic mouse model and a galectin-9 (Tim3 ligand) transgenic mouse model, an increase in MDSCs and inhibition of immune responses are observed [27]. Interestingly, we found that Tim3-hIg expressing therapeutic tumor vaccine did not exhibit an additive inhibitory effect on tumor growth when given in combination with 5-FU, which has recently been reported to selectively kill MDSCs and thus enhance antitumor immunity [33]. Second, Tim3 pathway inhibition may enhance anti-tumor immunity by antagonizing phagocytosis of apoptotic cells and thereby circumventing the immunosuppressive effect of apoptosis.…”
Section: Discussionmentioning
confidence: 66%
“…48 5-FU was also reported to increase IFN-g production by tumor-specific CD8 T-cells infiltrating the tumor, and to boost T-cell-dependent antitumor responses by in vivo elimination of MDSCs. 49 In both mouse models and patients with esophageal squamous cell carcinoma, neoadjuvant chemotherapy with 5-FU and cisplatin increased the intratumoral trafficking of CD4 and CD8 T-cells. 50,51 In experimental carcinogen-induced adenocarcinomas and fibrosarcomas, doxorubicin treatment enhanced tumor-specific proliferation of CD8 T-cells in tumor-draining lymph nodes (LNs) and promoted tumor infiltration of activated, IFN-g-producing CD8 T-cells.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 96%
“…68,69 Different strategies to achieve therapeutic depletion of suppressive cell subsets have been described so far. [70][71][72] Gemcitabine kills MDSCs, both in vitro and in vivo, 49,73 with no significant reduction in other cell subsets. The selective loss of MDSCs was accompanied by an increase in the antitumor activity of CD8 T and NK cells.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In subcutaneous and orthotopic cell line transplantation models, gemcitabine, 5-FU and doxorubicin directly induce splenic CD11b + Gr1 + MDSC apoptosis [53][54][55][56]. This chemotherapy-induced MDSC death increases the activity of cytotoxic T cells and contributes to tumor control.…”
Section: Innate Immune Cellsmentioning
confidence: 99%